A Community of Responsible and Integrated Pest Management. Issue 4 (30th June 2020) - Thomson, Allison; Coronel, Eric; Young, Kelly Murray
Abstract: This article is brought to you by the SPARC Initiative created in partnership between the American Society for Agronomy, the Agricultural Retailers Association, Environmental Defense Fund, and Field to Market: The Alliance for Sustainable Agriculture to empower trusted advisers to deliver services that drive continuous improvement in the productivity, profitability, and environmental outcomes of farmers' operations. Learn more about the SPARC Initiative and access additional resources, including the six‐module series on sustainability at www.fieldtomarket.org/SPARC . Earn 1 CEU in Sustainability by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/842 .